Generative AI for Software Practitioners - Ebert, Christof; Louridas, Panos; Ebert, Christof (IEEE software, 2023)
Generative artificial intelligence (AI) tools, such as Bard, ChatGPT, and CoPilot, have rapidly gained widespread usage. They also have the potential to boost software engineering productivity. In this article, we elaborate technologies and usage of generative AI in the software industry. We address questions, such as: How does generative AI improve software productivity? How to connect generative AI to software development, and what are the risks? Which technologies have what sorts of benefits? Practitioner guidance and case studies are shared from our industry context. I look forward to hearing from you about this column and the technologies that matter most for your work.—Christof Ebert